Medidas de prevención de la mycobacterium tuberculosis y su incidencia en pacientes adultos mayores que acuden a consulta externa del hospital El Empalme, de enero a junio del 2012 - Mendoza Cedeño, Rosario Trinidad (2013)
This research was conducted in the Canton province of Guayas The Junction, allows passage to the province of Los Rios, Manabi is located 167 kilometers from Guayaquil, Quevedo and 23 kilometers. The duration of this investigation was approximately 180 days. Our objectives are the following : a) Establish prevention methods that generates Mycobacterium Tuberculosis in older adults Hospital The Junction . b ) Specify the methods of prevention of Mycobacterium Tuberculosis in older adults . c ) Provide an educational campaign on the Mycobacterium tuberculosis among the inhabitants of the canton The Junction . The population for the implementation of this research was comprised of 2,870 patients attending the consultation area , according to the Hospital " The Splice " , giving as shown after applying the formula of probability with 5 % error of 226 patients were surveyed. As a result it was determined that 83 % of patients do not know how are the forms of transmission of tuberculosis , 100 % of people who come to the hospital The Junction , indicated that if they would participate in training to learn the methods of prevention of tuberculosis was considered feasible and viable development of the campaign to prevent TB